Enhancing Eighth Grade Students’ Active Participation with the Think-Pair-Share Strategy in English Language Learning at SMP Negeri 7 Kupang - Logha, Yohana; Toni, Elvis Albertus Bin (Universitas Pahlawan Tuanku Tambusai, 2026)
This study addresses the issue of low student participation in English as a Foreign Language (EFL) classrooms, which remains a persistent challenge in Indonesian secondary education. Although cooperative learning strategies have been widely promoted, there is limited research focusing on students’ active participation in junior high school EFL contexts, particularly in eastern Indonesia. This study aims to explore how the Think-Pair-Share (TPS) strategy enhances eighth-grade students’ active participation in English learning at SMP Negeri 7 Kupang and to examine students’ responses toward its implementation. Employing a qualitative case study design, data were collected through classroom observations, interviews, and documentation. The findings indicate that TPS significantly improves students’ behavioural, cognitive, and emotional participation by fostering collaboration, confidence, and engagement. Students also demonstrated a positive perception of the strategy. Overall, Think-Pair-Share is an effective approach for promoting active participation in EFL classrooms.